THE QUALITY OF POTATO TUBERS FOR THE PREPARATION OF CHIPS, DEPENDING ON THE GROWING TIME AND ELEMENTS CULTIVATION TECHNOLOGY - Begimkulov Ilkhom Bakhtiyorovich; Ganiyev Sanjar Ernazarovich; Turgunov Mirabdulla Dexkanovich; Khasanov Rasul Kurbanaliyevich; Tursunkulova Adiba Burxonovna; Raxmonov Raxmatullo Umaraliyevich (The Bioscan, 2024)
The article presents data on the study of the influence of varietal characteristics, timing of growing potatoes and plant placement patterns on the yield and quality of potato chips. It was established that tubers of the Ramona variety are more suitable than Surkhan-1 because of the content of more dry matter and starch. It is noted that during spring planting and with a sparse planting pattern of seed tubers, the tubers contain more dry matter and starch. This contributes to a higher yield and quality of the prepared chip.